2021
DOI: 10.18632/aging.203503
|View full text |Cite
|
Sign up to set email alerts
|

High-dose vitamin C ameliorates cardiac injury in COVID-19 pandemic: a retrospective cohort study

Abstract: Background: Cardiac injury is common and associated with poor clinical outcomes in COVID-19. Data are lacking whether high-dose intravenous vitamin C (HIVC) could help to ameliorate myocardial injury in the pandemic. Methods: The retrospective cohort study included consecutive severe and critically ill COVID-19 patients with cardiac injury receiving symptomatic supportive treatments alone or together with HIVC. Troponin I and inflammatory markers were collected at admission and day 21 during hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Furthermore, C-reactive protein (CRP), procalcitonin (PCT) and interleukin-8 (IL-8) concentrations were reduced in the patients with COVID-19 who received IVC. Other retrospective cohort studies from Wuhan, China, also reported reductions in inflammatory markers (CRP, IL-6, TNF-α) and ameliorated cardiac injury in patients with severe COVID-19 who had received a loading dose of 100 mg/kg bodyweight 6 hourly on the first day followed by 100 mg/kg 12 hourly for the following 5 days, relative to those who received standard therapy only [33,34]. Severe COVID-19 is mainly characterized by deteriorating respiratory function and rapid progression of radiological lesions, while the critical type requires mechanical ventilation and is accompanied by shock or multiple organ failure.…”
Section: Retrospective Cohort Studies With Intravenous Vitamin Cmentioning
confidence: 91%
“…Furthermore, C-reactive protein (CRP), procalcitonin (PCT) and interleukin-8 (IL-8) concentrations were reduced in the patients with COVID-19 who received IVC. Other retrospective cohort studies from Wuhan, China, also reported reductions in inflammatory markers (CRP, IL-6, TNF-α) and ameliorated cardiac injury in patients with severe COVID-19 who had received a loading dose of 100 mg/kg bodyweight 6 hourly on the first day followed by 100 mg/kg 12 hourly for the following 5 days, relative to those who received standard therapy only [33,34]. Severe COVID-19 is mainly characterized by deteriorating respiratory function and rapid progression of radiological lesions, while the critical type requires mechanical ventilation and is accompanied by shock or multiple organ failure.…”
Section: Retrospective Cohort Studies With Intravenous Vitamin Cmentioning
confidence: 91%
“…Although a few observational research and preliminary clinical studies on vitamin C in patients with COVID-19 corroborate their findings by noting a reduction in hyper inflammation (43,44,47), improvement in the oxygen support status (39,41,46,47), lower incidence of thrombosis (42), and also the reduced disease aggravation in the early stage of COVID-19 pneumonia (43), the mortality rate is still controversial among the studies. Some authors found a reduction in mortality (46) whereas other studies with vitamin C did not observe a difference in mortality when compared to patients in the control group (40,42,45).…”
Section: Vitamin Cmentioning
confidence: 87%
“…Among 108 coronavirus-associated melatonin articles extracted and assessed for eligibility, three studies with a melatonin approach were included (33)(34)(35). Moreover, among the 399 coronavirus-associated zinc studies extracted and evaluated for eligibility, three studies entered the inclusion criteria (36)(37)(38), whereas among 344 coronavirus-associated vitamin C (or ascorbic acid) papers initially extracted and analyzed for eligibility, a total of 10 papers were also included as RCTs or observational research (37,(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sub-group of patients with SOFA scores ≥ 3, the differences in ICU and hospital mortality were statistically significant while the 28-day mortality approached, but did not reach statistical significance (21.7% vs. 52.4%, P = 0.06) [ 81 ]. To date, there is only one small RCT involving IVAA demonstrating improved mortality in those patients with an SOFA score ≥ 3, and there has been accumulating evidence that IVAA improves inflammatory markers, coagulopathic parameters, ameliorates cardiac injury, decreases incidence of systemic inflammatory response syndrome (SIRS) and shortens the duration of SIRS ( Table 3 ) [ 81 - 89 ].…”
Section: Aa and Covid-19mentioning
confidence: 99%